Por que meu vô chorava: a clínica da depressão - Freitas, Roziliane Oesterreich de (2018)
Why my grandfather cried: the depression clinic - was built from clinical experience with diagnosed depressed patients using psychiatric medication. It is not, as the title might suggest, a response to my grandfather's experience of depression; but rather as an inspiration for the study of the clinic of depression to take its own shape. Thinking of depression in the light of Psychoanalysis, considering its genesis, the sense of symptoms, the differential clinic in relation to other neuroses and pathologies, required bringing together authors of relevant studies in the field of Psychoanalysis, especially the study published by Maria Rita Kehl, for translating what I was undertaking in listening to the depressions of patients referred by psychiatrist (colleagues) friends. To preserve the progress of patient analyzes, I have used literary references as approximate examples of the types of depression that depress neurotics. We know that not only do neurotics suffer from depression; in this study, however, experience and theoretical and literary references point to three types of depression: depression in hysterical neurosis, obsessional neurosis, and the type that contains a rarity of understanding, that of neurotic depression. It is in the dimension of its psychic structure that the listening of the suffering of the depressive affects in the scope of the clinical treatment. Finally, the difficult question of the clinical conduct of depression, especially of severe cases, accompanied by psychiatric medication